Improvement of the methodological approach to assessing the impact of public governance on ensuring the economic security of the state - Akimova, L.; Akimov, O.; Mihus, I.; Koval, Ya.; Dmitrenko, V.; Мігус, Ірина Петрівна (FINTECHALLIANCE LLC, 2020)
Ensuring economic security is a guarantee of independence and autonomy of the state, an integral condition for stability and effective functioning of society. Given the development of the world economy, ensuring the economic security of Ukraine, which is the basis of national security, is becoming an increasingly urgent problem. The formation of the system of economic security of Ukraine takes place in the conditions of economic globalization, which can not but affect the national interests and trends of socio-economic development of the country. It is to address this result that the issue of regulating the role and place of economic security in the general system of public administration mechanisms in Ukraine arises. In today’s realities there is a negative trend of increasing influence of external and internal threats on the activities of the state and its management. The modern concept of state development provides a single set of requirements for its institutions: openness of legal and economic systems; transparency of the mechanism of public administration, its economic, legal and information support; protection of economic interests of the state, social protection of life and health of the population, etc. Improving the management of economic processes in the state should begin with the development of a clear procedure and mechanisms for identifying and neutralizing threats in the system, which will contribute to the development of effective economic policy, state control over the socio-economic system, objective prioritization of economic reform, etc. Assessment of the current state of economic regulation has revealed that the main energy of the executive branch is spent not on overcoming the causes that provoke illegitimate phenomena, but on combating their consequences, so it requires the development of effective mechanisms for public administration of economic security.
Keywords: evaluation; public administration; economic security; state; methodological approach